Mental Health Management in the Health Care System: A Psychological Perspective - Karyono, Septin Maisharah (PT. Anagata Sembagi Education, 2024)
Mental health is an important component in achieving an individual's overall well-being. However, mental health services are often separated from physical health services, creating significant gaps in the healthcare system. Integration of mental health services into the physical healthcare system is a major challenge that must be overcome to create a holistic approach to healthcare. Strong social stigma towards mental health remains a major barrier, which prevents individuals from accessing the services they need. In addition, access to mental health services, especially in remote areas, is still limited due to lack of expertise and unequal distribution. An integrated approach, involving multidisciplinary coordination between various health professions as well as the utilization of technology, such as telecounseling and digital applications, can expand the reach of services. In addition, strong policy support and investment in digital infrastructure development are needed to accelerate the implementation of more equitable and inclusive services. Collaboration between the government, health workers, and communities is a strategic step to overcome this challenge. With strong synergy and the elimination of stigma, a more effective and sustainable mental health system is expected